Casey Would! Dr. Casey A. Wood, the McGill Library's Forgotten Benefactor - Lyons, Christopher (Papers of the Bibliographical Society of Canada / Cahiers de la Société bibliographique du Canada, 2022)
The world-renowned physician, bibliophile, and McGill alumnusSir William Osler (1849–1919) wrote that “a library represents the mind of its collector, his fancies and foibles, his strength and weakness, his prejudices and preferences.”* Osler’s own collection of medical and related works formed the nucleus of McGill’s Osler Library of the History of Medicine. Opened in 1929, the Osler Library is renowned for both its collection and the preservation of its founder’s memory and ethos. In 1920, Dr. Casey Wood (1856–1942), a friend and contemporary of Osler’s, created the Wood Library of Ornithology and the Blacker Library of Zoology at McGill. The rare natural history material from these two libraries, now the Blacker-Wood Natural History Collection in the university’s Rare Books and Special Collections, rivals the Osler in its depth and rarity. Despite this, its founder remains largely unknown. Although it is understandable—Osler was as famous and loved as Wood was aggressive, overbearing, and vain—it is unfortunate. Wood devoted tremendous energy, drive, and money, over decades, to build one of the best natural history collections around. He also hoped that these libraries would engage in public education and encourage people to respect and enjoy the natural world. Although he could be an unpleasant person, it is useful to know something about the man whose collection so strongly bears his stamp.